Designed porous microstructures for electrochemical reduction of bulk hematite ceramics. (15th May 2017) - Ivanova, Yu.A.; Monteiro, J.F.; Teixeira, L.B.; Vitorino, N.; Kovalevsky, A.V.; Frade, J.R.
Abstract: This work proposes a new approach for electrochemical reduction of hematite to magnetite and/or metallic iron, based on ceramic cathodes with designed microstructures. The processing method, involving emulsification of concentrated aqueous ceramic suspensions with melted paraffin, enables preparation of cellular hematite ceramics possessing open porosity and pore interconnectivity controlled by simple process parameters. The obtained porous hematite ceramics were successfully used as cathodes for in situ electrochemical reduction in aqueous alkaline electrolyte. Electrochemical reduction converts the designed ceramic microstructure to corresponding cellular Fe/Fe3 O4 /Fe2 O3 composites with adjustable phase distributions and high prospects for applications in heterogeneous catalysis or other applications, based on unique combinations of active functionalities of metallic Fe, magnetite and hematite. Graphical abstract: Highlights: Controlled tuning of microstructure in hematite ceramic cathodes is achieved. Cathodic reduction of designed cellular ceramics is performed in aqueous medium. Cellular Fe/Fe3 O4 /Fe2 O3 composites are obtained from hematite ceramic cathodes.